Las masacres de Río Negro: reflexiones sobre el genocidio de las comunidades indígenas y la obligación de investigar, juzgar y castigar - Núñez Marín, Raúl Fernando (2023)
The defense of human rights at the international level involves the analysis of various concepts, such as genocide and crimes against humanity, that are drawn from disciplines like international criminal law. The Inter - American syste m of human rights has not been immune to this phenomenon because of the atrocious acts that took place in the 1970s and 1980s in Central and South America. The case of Guatemala is revealing of the human rights violations that indigenous communities have s uffered in the context of domestic armed conflict. A clear example of this is the case of the Río Negro massacres analyzed here through an amicus brief filed with the Inter - American Court of Human Rights.